Effect of fermentation on sensory quality of Liberica coffee beans inoculated with bacteria from saliva Arctictis binturong Raffles, 1821 - Nendyo Adhi Wibowo; WIBOWO MANGUNWARDOYO; YASMAN YASMAN; TRI JOKO SANTOSO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Wibowo NA, Mangunwardoyo W, Santoso TJ, Yasman. 2021. Effect of fermentation on sensory quality of Liberica coffee beans inoculated with bacteria from saliva Arctictis binturong Raffles, 1821. Biodiversitas 22: 3922-3928. Fermentation is one of the post-harvest steps that influence the quality of coffee. This study aims to determine the sensory quality of Liberica coffee beans cv. Liberoid Meranti (LiM) fermented using a consortium of bacteria from saliva Arctictis binturong Raffles, 1821 with varying fermentation periods. Fermentation was performed in a wet process for 0, 4, 8, 12-hours in triplicate. The parameters observed were caffeine, protein, and fat content. The sensory quality of brewed coffee was conducted refers to the standard Speciality Coffee Association (SCA). The data obtained were processed with Minitab version 16 for Windows and analyzed using ANOVA with a level of 5% and followed by a post hoc test. The results showed that coffee fermented for 0, 4, 8, 12 hours has protein content of 15.31-15.67%; 15.09-16.62%; 12.71-13.07%; 14.64-14.69%; fat content of 9.48%; 10.20%; 9.96%; 10.21%; and caffeine content of 1.05%; 0.99%; 0.96%; 1.02%, respectively. The length of the fermentation period affects significantly (p<0.05) the content of protein, fat, and caffeine. The final score of cupping test in coffee fermented for 0, 4, 8, and 12 h were 77.63; 78.13; 82; and 80.25, respectively. A fermentation period of 8 and 12 hours improve the flavor score that categorized fermented Liberica coffee as specialty coffee (8.00 - <9.00 = superior).